Bullfighting broadcasts in Telecinco and Antena3 (1990-2010) - de Haro de San Mateo, María Verónica (Estudios sobre el Mensaje Periodístico, 2020)
A quantitative and qualitative study of bullfighting broadcasts in Antena3 and Telecinco (1990-2010) is offered based on the viewing of broadcasts; interview with professionals from the audiovisual and bullfighting sector; the analysis of bibliographic / hemerographic sources and audience metrics yearbooks. It is concluded that the networks that starred in the bullfighting boom in the mid-1990s: 1) bet on the broadcasting of bullfighting shows in their programmatic strategy to obtain an audience taking advantage of their popularity among viewers; 2) they promoted the “media bullfighters” (who, although they benefited from a great projection, also suffered criticism from the specialized press and the more orthodox sector of the fans); 3) aggravated the historical disunity of bullfighting estates with the conflict of image rights; and 4) projected a distorted vision of the bullfight that, in the medium term, harmed bullfighting industry and its actors.